Health Inequities in Historical Context: A Critical Race Theory Analysis of Diabetes among African Americans and American Indians - Mitchell, Felicia M. (Race and social problems, 2020)
African Americans and American Indians experience disproportionately high rates of Type 2 diabetes mellitus (T2DM) and are approximately two times as likely to be diagnosed with T2DM as non-Hispanic Whites in the United States (U.S.). African Americans and American Indians represent unique populations in the U.S., as they are the descendants of entire peoples who were forcibly relocated to/within the U.S, and seized under U.S. rule. Research indicates that being a member of particular racial or ethnic groups influences an individual’s diabetes risk and one’s overall health. However, much of the research on T2DM has focused on the individual prevention of or risk of developing diabetes. In contrast, there is a limited review of the impact of shared historical and contemporary experiences of marginalization and the role they have in racial and ethnic health inequities. More so, African American and American Indian health inequities are typically examined in isolation from one another or within the context of settler colonial norms, despite their irrefutably shared historical experiences. This study builds on the diabetes literature by examining T2DM in African Americans and American Indians using an analytical framework informed by both Critical Race Theory and Tribal Critical Race Theory. Using data from the California Health Interview Survey (CHIS), this study conducted a secondary data analysis of multilevel factors contributing to T2DM among African American and American Indian adults residing in California. Findings indicate that both individual- and structural-level factors are linked to diabetes diagnosis and management. Implications for future research are discussed.